Repeat Kidney Transplantation After Failed First Transplant in Childhood. Issue 8 (August 2015) - Gupta, Meera; Wood, Alexander; Mitra, Nandita; Furth, Susan L.; Abt, Peter L.; Levine, Matthew H.
<x xml:space="preserve">Abstract</x> Background and Objectives Kidney transplant graft survival is almost uniformly superior for initial transplants compared to repeat transplants. We investigate the association between first second kidney transplant graft survival in patients who underwent initial transplant during their pediatric years whether age at second transplant is associated with outcome. Design, Setting, Participants, and Measurements This is a retrospective analysis of Organ Procurement and Transplantation Network data from October 1987 to May 2009 examining second kidney graft survival in 2281 patients who received their first transplant at younger than 18 years using Kaplan-Meier statistics. Factors associated with second graft survival were identified using a multivariable Cox proportional hazards model. Results Patients with first kidney graft survival of less than 5 years had better second graft survival compared to patients with first graft survival of 30 days to 5 years (P < 0.01). Patients with first kidney graft survival less than 30 days had similar second kidney graft outcomes(P = 0.50) as those with longer than 5 years first kidney graft survival, demonstrating that very early first graft loss is not associated with poor second transplant outcome. Patients 15 to 20 years of age at second transplant have lower second graft survival compared to other age groups; P less than 0.01, regardless of other recipient/donor characteristics and recurrent disease. Conclusions Poor second transplant outcomes are identified among patients with previous pediatric kidney transplant with first graft survival longer than 30 days, but shorter than 5 years, and those receiving second transplants at a high-risk age category (15-20 years). These groups may benefit from increased attention both before and after transplantation.